2016
DOI: 10.1016/j.psyneuen.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal testosterone predicts sex-related differences in early expressive vocabulary

Abstract: During the first few years of life, girls typically have a larger expressive vocabulary than boys. This sex difference is important since a small vocabulary may predict subsequent language difficulties, which are more prevalent in boys than girls. The masculinizing effects of early androgen exposure on neurobehavioral development are well-documented in nonhuman mammals. The present study conducted the first test of whether early postnatal testosterone concentrations influence sex differences in expressive voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…These largely negative results could reflect the small sample and the use of language measures that did not show substantial gender differences. Another study from a different team found that testosterone measured in saliva samples from 36 boys and 42 girls at aged 1 to 3 months significantly predicted scores on a measure of expressive vocabulary at aged 18 to 30 months [23]. In this study, the measures of testosterone and of expressive vocabulary both showed significant sex / gender differences, and the significant correlation between testosterone and expressive vocabulary was seen in both the boys and the girls, separately.…”
Section: Early Postnatal Testicular Activation: Mini-pubertysupporting
confidence: 47%
“…These largely negative results could reflect the small sample and the use of language measures that did not show substantial gender differences. Another study from a different team found that testosterone measured in saliva samples from 36 boys and 42 girls at aged 1 to 3 months significantly predicted scores on a measure of expressive vocabulary at aged 18 to 30 months [23]. In this study, the measures of testosterone and of expressive vocabulary both showed significant sex / gender differences, and the significant correlation between testosterone and expressive vocabulary was seen in both the boys and the girls, separately.…”
Section: Early Postnatal Testicular Activation: Mini-pubertysupporting
confidence: 47%
“…Kung et al . () found that salivary testosterone levels measured at 1 to 3 months of age were negatively correlated with expressive vocabulary at 16 to 30 months, and that they mediated the higher values in girls than in boys at this age, suggesting that any differences cannot be attributed to the slower development of boys than girls. There is some evidence from adults that verbal fluency is lower when circulating testosterone levels are higher: for example, a negative correlation in a large sample ( N = 1276) of women aged 35 to 90 years (Table in Thilers et al, ); a decline following 3‐months of testosterone administration in female‐to‐male transsexuals (van Goozen et al, , ); and an improvement when women's testosterone levels were reduced in a small clinical sample (Schattmann & Sherwin, ).…”
Section: Social Relations and Related Attributesmentioning
confidence: 97%
“…cognition (Macnamara, ; Harris, ; Ellis, ); personality (Daly, ; Koppensteiner & Grammer, ; de Vries et al ., ); empathy (Håkansson & Montgomery, ; Miller & Wallis, ; Derksen, Bensing & Lagro‐Janssen, )] and, on the other hand, between human communication and physiological factors [e.g. hormones (Carney, Cuddy & Yap, ; Hahn et al ., ; Kung et al ., ); cardiovascular reactivity (Thomas & Liehr, ; Brondolo et al ., ; Hulsman et al ., ); see also Honeycutt, Sawyer & Keaton, for a review]. Human communication can also be influenced by physical (e.g.…”
Section: Theories Of the Origins Of Languagementioning
confidence: 99%